Inovasi Aplikasi Pariwisata Cerdas: Penyewaan Layanan Pemandu Wisata di Lembang - Mohamad Dicky Syahputra; Irman Hariman (Journal Data Science, Technology, Informatics and Security, 2023)
This research aims to address the primary challenges in Indonesia's tourism industry, notably the lack of accessibility to accurate information and references. Employing a qualitative approach and Extreme Programming (XP) methodology, the study emphasizes the importance of integrating tour guide services with other tourism services. As a solution, the research proposes the "Smart Tourism" system, which amalgamates various tourism services into a comprehensive application, introducing the concept of a one-stop solution holiday. The research findings demonstrate that this application facilitates tourists in booking tour guide services and other amenities while providing customizable options for users. Supported by a collaborative filtering user-based decision support system (DSS), it enhances user experiences and contributes to the economic growth of regions. Consequently, this research significantly impacts the transformation of the tourism travel paradigm, unifying tourism services, enriching tourists' experiences in Indonesia, and aligning with the vision of a more integrated smart city. This contribution extends beyond the tourism sector, fostering the overall economic development of regions.